Hubungan antara Pola Pembuangan Sampah dan Risiko Pencemaran Lingkungan terhadap Kesehatan Mayarakat: The Relationship between Waste Disposal Patterns and the Risk of Environmental Pollution to Public Health - FILZARICHA ARDHITA; USIONO (JURNAL ILMIAH NUSANTARA, 2025)
One of the common causes of environmental pollution in many areas, especially in urban areas, is improper waste disposal. This study aims to evaluate the relationship between waste disposal patterns, environmental pollution risks, and their impact on public health. Therefore, the data in this study were collected through a survey of 200 residents living in areas with various waste disposal patterns. The results of this study show that poor waste disposal patterns are closely related to the risk of water, air, and soil pollution. This, in turn, will increase the number of cases of diseases such as diarrhea, skin diseases, and other respiratory diseases. This research recommends the need for further efforts to combat environmental pollution and maintain public health.